2017
DOI: 10.21037/tgh.2017.07.02
|View full text |Cite
|
Sign up to set email alerts
|

Management of gastric cancer in Indian population

Abstract: Adenocarcinoma stands the most common malignancies in the gastric carcinomas and holds a significant mortality and morbidity rates annually, due to the early vague symptoms among the population and hence the delayed presentation at advanced stages of cancer. In India the screening programs for gastric cancer has been a setback due to various logistics reasons and the data available from reporting is also not content. Our study is a review article featuring the management of gastric cancer in the Indian populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Highest incidence was reported in Eastern Asia, South America, and Central Europe. 21 Gastric cancer patients are treated with chemotherapy as the first choice of treatment, but it leads to serious side effects and the survival rate was also not increased in most cases. 22 Hence, alternative medicine is the need of today to treat cancer, and phytomedicine is once such field that shows promising evidence to treat cancer with less or nil side effects compared to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Highest incidence was reported in Eastern Asia, South America, and Central Europe. 21 Gastric cancer patients are treated with chemotherapy as the first choice of treatment, but it leads to serious side effects and the survival rate was also not increased in most cases. 22 Hence, alternative medicine is the need of today to treat cancer, and phytomedicine is once such field that shows promising evidence to treat cancer with less or nil side effects compared to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies, the NAs, mainly NDMA, were found in food cooked by the direct flame heating method. The NAs, especially NDMA, were present in barley used for making beer and coffee roasted in direct flame heated air as well as in meat that was roasted, broiled, grilled, baked or deep fried in open furnaces [33][34][35]. The following mechanisms for the formation of NDMA were proposed.…”
Section: Discussionmentioning
confidence: 99%
“…GC, being the fifth most commonly occurring cancer, is prevalent in the eastern and central parts of Asia and is the third most common cancer as per the mortality rate [3,4]. Mizoram, Northeastern tribal state of India has the highest incidence rate of gastric cancer in India [5] and globally occupies the fifth position for GC [6].…”
Section: Introductionmentioning
confidence: 99%